Foreign and public deficits in Greece: In search of causality - Michalis Nikiforos; Laura Carvalho; Christian Schoder (Levy Economics Institute of Bard College, 2013)
This paper analyzes the trajectories of the Greek public deficit and sovereign debt over the last three decades and their connection to the political and economic environment, paying special attention to the causality between the public and the foreign deficit. The authors argue that, from 1980 to 1995, causality ran from the public deficit to the foreign deficit but has since reversed, a result of the European monetary unification process and the adoption of the common currency. This hypothesis is tested and verified econometrically using the Granger causality and cointegration analyses.
Keywords: E62; F21; F34; F41; 330; Greece; crisis; public debt; twin deficits; imbalances